A Class of Periodic Solutions of One-Dimensional Landau-Lifshitz Equations (Journal of Mathematical Study, 2017)
We study one-dimensional Landau-Lifshitz Equations and give the sufficientand necessary conditions for the existence of a class of periodic solutions.
Keywords: Landau-Lifshitz; periodic solution; blow up.